2009
DOI: 10.1111/j.1365-2265.2008.03337.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10–592C/A, –819C/T and –1082A/G promoter variants affect the susceptibility to nephropathy in Tunisian type 2 diabetes (T2DM) patients

Abstract: This study suggests that IL-10 promoter polymorphism influence the risk of nephropathy in Tunisian T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…IL-10 levels increased in IL-10-(−592C/C) genotype compared to IL-10-(−592A/A) and IL-10-(−592A/C) genotypes in DN patients while such difference was not found in T2DM patients without nephropathy. Similar to our findings, IL-10-(-592C/A) genotype distribution didn't differ between T2DM patients with or without nephropathy and IL-10 (-592C/A) genotype revealed significant association with cytokine expressions in DN patients [9,14,15]. Twenty-eight polymorphisms occur in the promotor region of IL-10 gene, these polymorphisms were found to affect gene transcription and expression.…”
Section: Discussionsupporting
confidence: 78%
“…IL-10 levels increased in IL-10-(−592C/C) genotype compared to IL-10-(−592A/A) and IL-10-(−592A/C) genotypes in DN patients while such difference was not found in T2DM patients without nephropathy. Similar to our findings, IL-10-(-592C/A) genotype distribution didn't differ between T2DM patients with or without nephropathy and IL-10 (-592C/A) genotype revealed significant association with cytokine expressions in DN patients [9,14,15]. Twenty-eight polymorphisms occur in the promotor region of IL-10 gene, these polymorphisms were found to affect gene transcription and expression.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have also investigated the role of IL-10 polymorphisms in the development of diabetic nephropathy; however, the results of these studies are inconsistent (Babel et al, 2006;Ezzidi et al, 2009;Mtiraoui et al, 2009;Arababadi et al, 2012;Erdogan et al, 2012). Babel et al (2006) reported an association between the GG genotype of the IL-10 -1082G/A polymorphism and an increased susceptibility to end-stage renal disease in German patients.…”
Section: Discussionmentioning
confidence: 99%
“…Babel et al (2006) reported an association between the GG genotype of the IL-10 -1082G/A polymorphism and an increased susceptibility to end-stage renal disease in German patients. Similarly, Ezzidi et al (2009) reported an association between the T allele of IL-10 -819T/C and the development of type 2 diabetes in a Tunisian population, while Mtiraoui et al (2009) summarized that genetic variations in the IL-10 promoter could affect the risk of nephropathy in patients with type 2 diabetes. Kung et al (2010) also reported a significant association between the -592A/C polymorphism in IL-10 and type 2 diabetic nephropathy, via altered IL-10 production.…”
Section: Discussionmentioning
confidence: 99%
“…Amre et al (2009) conducted a study on 270 patients with Crohn's disease and 336 control subjects, and reported that IL-10 -819C/T variants contributed to the onset of Crohn's disease. Several studies have reported the possible correlation between polymorphisms in IL-10 and the onset of type 2 diabetes mellitus, but with conflicting results (Ezzidi et al, 2009;Saxena et al, 2012Saxena et al, , 2013Yin et al, 2013;Bai et al, 2014;Chang et al, 2005). Chang et al (2005) reported that IL-10 polymorphisms could determine diabetic susceptibility in a Taiwanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (2005) reported that IL-10 polymorphisms could determine diabetic susceptibility in a Taiwanese population. Ezzidi et al (2009) performed a study on 515 patients with type 2 diabetes and 402 control subjects, and discovered a correlation between the IL-10 -819C/T polymorphism and the risk of nephropathy in a Tunisian population. Furthermore, Saxena et al (2012Saxena et al ( , 2013 reported that Indian patients harboring the IL-10 -592C/A polymorphism displayed a greater risk of developing type 2 diabetes mellitus compared to that by the controls.…”
Section: Discussionmentioning
confidence: 99%